Inside Cover: Catalysis of Vanadium Ion Redox Reactions on Carbonaceous Material with Metal–N4 Sites (ChemCatChem 15/2015). Issue 15 (3rd August 2015) - Maruyama, Jun; Hasegawa, Takahiro; Iwasaki, Satoshi; Fukuhara, Tomoko; Orikasa, Yuki; Uchimoto, Yoshiharu
<x xml:space="preserve">Abstract</x> The Inside Cover shows a color‐matching game with colored balls supplied from tanks. Purple, green, blue, and yellow correspond to the colors of the vanadium ion solutions. The balls react on the catalysts when the colors (redox potentials) match the catalyst. In their Communication, Maruyama and co‐workers describe that matching the redox potentials of the vanadium ion species with the metal species embedded on a carbonaceous material surface with nitrogen atoms resulted in catalytic activity for redox reactions. Regarding the dioxovanadium ion (VO2+) reduction, Fe was the active metal, and the VO2+ reduction behavior indicated that the reduction proceeded through an inner‐sphere mechanism involving the hydroxyl group attached to the central Fe atom, in contrast to the outer‐sphere mechanism for other metals and conventional carbon electrodes. The article highlighted by this cover can be found on p. 2305 ff. of Issue 15, 2015.